COVID-19: Psychological impact and solution - Ha, Ly Hong Huong; Nhut, Nguyen The; Yen, Nguyen Thi Hong; Trĩnh, Tran Trung (Tạp Chí Khoa học Trường Đại học Quốc tế Hồng Bàng, 2021)
The COVID-19 pandemic is a major pandemic that is a matter of concern all over the world. In the face of the current complex and dangerous situation, living with and coping with the pandemic is essential to sustaining the economy and other foundations. The COVID-19 pandemic has not only impacted physical health, but also psychological health. Protecting yourself and your family’s well-being is the top priority for helping the people around you to cope with and overcome the COVID-19 pandemic. This report will introduce some methods of treating COVID-19 with mental therapy in order to maintain the spirit of living together and facing the pandemic more effectively.